Group Delay Optimization in Cascaded Optical Ring Ressonator-based Optical Beamforming Networks - Herminarto Nugroho (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2021)
Cascaded optical ring resonator-based optical beamforming networks can be used to optimize the signal power received by planes. This is essential for airplanes-sattelite communication as a solution for a high-speed internet access inside airplanes cabin. This system relies on phased array antenna (PAA), an array of a very small and flat antenna elements which will receive a time-delayed version of desired signal from specific angle. The delay time will create phase differences between each received signal, and in consequence, lower the signal power. We propose a method to optimize the group delay of the received signals in order to obtain maximum signal power. We simulate the optimization algorithm using a set of data, which consists of full input signals. To analyze the accuracy, the desired signal is known explicitly. Given the configuration of OBFNs and all nominal parameters required, it was verified in simulation that the optimization algorithm can be used to tune optical beamforming networks for any group delays.